INTERNET HELPS PEOPLE IN DELIVERING INFORMATION WITHIN THE COMMUNITY IN INDONESIA AS A DEVELOPING COUNTRY - Murdiani, Trufi (Prosiding International conference on Information Technology and Business (ICITB), 2015)
In the past time when ancient kingdoms still exist, Indonesian people have some unique methods in communicating and announcing important news of information in community. In the villages and some small cities, people applied these ancient communicating methods. Itâs affective and cheap on cost. Until nowadays, those methods are still common. There is one most ancient method to announce information that related with community interest. The village leader goes to religion house such as mosque, church, or temple. Another way is implemented by knocking bamboo gong. For each sound of bamboo gong represents the vary occurred events such as the sounds for many times knocking is to fire, sounds with a bit long and a few times is to announce a theft case, different sounds are to inform citizens about the volcano eruption, flood, earthquake and other kind of disasters. Currently, when the internet era is emerging, the method to informing something important in the community is also done by internet. Moreover, Indonesia with area of 1,919,440 kilometer squares with 35 provinces and as an island country is a very big country in terms of range and population. The existence of internet eases the delivering information in the community. Â  KEY WORDS: information, ancient method, internet. Â